Analyze Different Theories of Justice, Considering Global Resource Distribution, The Responsibility to Intervene, And the Role of International Cooperation (International Journal of Food and Nutritional Sciences, 2022)
The main goals of this study are how global justice is conceptualized and measured. The paper also explores the many theories, notions, evaluation guidelines, and approaches connected to the field of global justice research. The aim of this research is to enhance comprehension of the conceptualization of global justice, the selection and theoretical justification of conceptual indicators, and the conceptual consistency of those indicators with the notion of global justice. Global justice is a wide concept with many components that align with moral and empirical facts. These features are multifaceted and multilevel at different levels. Understanding the concept of justice can be difficult at times, yet it can also be easy at others. In a civilized community, what is deemed just for one individual need not be the same for other individuals. Scholars have not only tried to define justice at different times in history, but they have also helped to establish a wide range of theories related to justice. People who reside in distinct regions may view justice differently than people who reside in other regions. This study project focuses on examining a broad variety of justice-related characters and offers a thorough examination of how justice is portrayed in Rawls and Nozick's respective conceptions of justice.